1977
DOI: 10.1002/pi.4980090103
|View full text |Cite
|
Sign up to set email alerts
|

Glass transition temperatures of poly N — (N — alkyl)—maleimides

Abstract: The glass transition temperatures (T,s) of a series of poly N-(n-alkyl) maleimides covering only the even members with side chains ranging in length from ethyl to n-octadecyl have been studied from room temperature to above T,. T,s and thermal quantities have been determined from the specific volume-temperature relations only for the higher (n = 8, 10, 12, 14, 16 and 18, where n = n o of CH2) members of the series. However for the lower ones (n = 2 , 4 , 6 , 8 and 10) T,s have been detected from heat capacityt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…The jump may be tentatively rationalized in terms of: (i) an artefact; it is interesting to note that the width of the trace associated to the T g increases with decreasing mesogen content. However, we have used the same protocol62 through all the series to define T g , therefore it would only produce an additional but continuous drift and not a jump. (ii) An abrupt change in the smectic field (SF) as a result of a change in concentration of the n ‐octadecyl side‐chains within the non‐mesogenic comonomer in the neighborhood of the mesogenic moieties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The jump may be tentatively rationalized in terms of: (i) an artefact; it is interesting to note that the width of the trace associated to the T g increases with decreasing mesogen content. However, we have used the same protocol62 through all the series to define T g , therefore it would only produce an additional but continuous drift and not a jump. (ii) An abrupt change in the smectic field (SF) as a result of a change in concentration of the n ‐octadecyl side‐chains within the non‐mesogenic comonomer in the neighborhood of the mesogenic moieties.…”
Section: Resultsmentioning
confidence: 99%
“…T Cl and T m were taken to be at the maxima of the endotherms. Glass transition temperatures were located at the middle of the change in the heat capacity trace 62. All copolymers and two homopolymers samples were submitted to the same thermal history, that is, after the first heating scan, the samples were then annealed at 10 K above the isotropic temperature for 10–15 min.…”
Section: Methodsmentioning
confidence: 99%
“…In making a crude assumption, the viscosity for a rigid noninteracting sphere model is = 26.69 1/2 1/2/ 2 (24) where = hard-sphere diameter in angstroms. Values of for nonpolar molecules can be calculated from the relation of to critical constants through the equation = (2.44 -u'HT'/PJ1'* (25) where ' is the acentric factor which is defined as51 ' = 0.006R + 0.02087 2 -0.00136 3 (26) and R is the radius of gyration in angstroms. Values for R were taken from Reid, Prausnitz, and Sherwood.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26] The poly(RMI)s as the corresponding homopolymers with similar N-alkyl substituents were reported to exhibit high-T g values over the high temperature range from 97 °C for poly(ODMI) to 138 °C for poly(OMI). [27][28][29] The poly(RMI-alt -IB)s containing a long-alkyl side-chain exhibited the crystallization of their side groups, and consequently, the melting temperatures ( T m ) were observed of methanol and diethyl ether to precipitate the copolymer of the RMIs and PEGMI, respectively. The copolymers were fi ltered out, washed, and then dried in vacuo.…”
Section: Synthesis and Thermal Properties Of Poly (Rmi-alt -Ib)smentioning
confidence: 99%
“…increase in the T g values of the obtained copolymers, but simultaneously it induced another problem of the brittleness of the copolymers. Previously, Barrales-Rienda and co-workers [ 27,28 ] and Matsumoto et al [ 29 ] reported that the T g values decreased according to an increase in the carbon number of the N-n -alkyl groups of the poly(RMI)s. Furthermore, it was pointed out that the semifl exible mainchain suppressed side-group crystallization due to their restricted mobility of the segments, [29][30][31][32] while the side alkyl chains introduced into common comb-like polymers with a fl exible main-chain readily crystallized accompanying the reconstruction of main-chain conformation. [33][34][35] In this study, we synthesized maleimide copolymers with a low-T g value by the introduction of fl exible and linear substituents into the side groups and characterized the thermal and viscoelastic properties of the copolymers consisting of a rigid main-chain and fl exible side chains.…”
mentioning
confidence: 97%